2016
DOI: 10.1002/ijc.29994
|View full text |Cite
|
Sign up to set email alerts
|

WCRF/AICR recommendation adherence and breast cancer incidence among postmenopausal women with and without non‐modifiable risk factors

Abstract: Taller height, family history of breast cancer, greater number of years of potential fertility and nulliparity are established non-modifiable risk factors for postmenopausal breast cancer. Greater adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) diet, physical activity and body weight recommendations has previously been shown to be associated with lower breast cancer risk. However, no prior studies have evaluated whether women with non-modifiable risk factors recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 47 publications
6
80
3
Order By: Relevance
“…In addition to overall cancer incidence, eight studies reported results for female breast cancer incidence as an outcome (25, 27, 32-35). Consistent reductions in breast cancer incidence were demonstrated in the WHI, NIH-AARP, and EPIC cohorts for high adherence to nutrition and physical activity cancer prevention guidelines versus low adherence, with HRs (95% CIs) of HR=0.78, 95% CI: 0.67-0.92 (25), HR=0.81, 95% CI: 0.76-0.87 (27), and HR=0.84, 95% CI: 0.78-0.90, respectively (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to overall cancer incidence, eight studies reported results for female breast cancer incidence as an outcome (25, 27, 32-35). Consistent reductions in breast cancer incidence were demonstrated in the WHI, NIH-AARP, and EPIC cohorts for high adherence to nutrition and physical activity cancer prevention guidelines versus low adherence, with HRs (95% CIs) of HR=0.78, 95% CI: 0.67-0.92 (25), HR=0.81, 95% CI: 0.76-0.87 (27), and HR=0.84, 95% CI: 0.78-0.90, respectively (28).…”
Section: Resultsmentioning
confidence: 99%
“…Meeting each additional guideline was associated with a 5% (HR=0.95, 95% CI: 0.91-0.98) or 6% (HR=0.94, 95% CI: 0.91-0.98) reduction in breast cancer incidence utilizing the WCRF/AICR and ACS recommendations, respectively (34). Most recently, Nomura et al (35) evaluated adherence to the WCRF/AICR guidelines and breast cancer incidence among postmenopausal women with and without non-modifiable risk factors in the Iowa Women’s Health Study (IWHS) (n=36,626). The eight point adherence score was collapsed into 4 categories: 0-3.5 points (low adherence), 4.0-4.5, 5.0-5.5, 6.0-8.0 (high adherence).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, earlier studies reported strong inverse association with breast cancer risk. Estimates ranged from HR: 0.40 (95% CI: 0.25–0.65) (27) to HR: 0.76 (95% CI: 0.67–0.87) (29) comparing the adherence to more than five and six recommendations vs. 1 and 0, respectively. These discrepancies in results with previous studies may be explainable by different reference categories used.…”
Section: Discussionmentioning
confidence: 99%
“…Gramling et al (2010) reported from the Women’s Health Initiative study that participating in healthy behaviors (higher physical activity, low alcohol intake and appropriate body weight) was beneficial for risk reduction in postmenopausal women and the degree of this benefit was the same for women with or without a family history of BC. Recent work by Nomura et al (2016) has also reported that adherence to cancer prevention guidance (WCRF/AICR) is associated with lower breast cancer risk regardless of non-modifiable (taller height, family history of breast cancer, greater number of years of potential fertility and nulliparity) risk factor status.…”
Section: Introductionmentioning
confidence: 99%